Development of Connected Speech in Preschool Age Children Terms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the development of a child's speech in conjunction with the formation of his thinking, and most importantly, the need for comprehensive care, support for speech, and the need to help form a rich and stable internal content in the minds of children, as well as the successful development of coherent speech in older preschool children. The conditions are discussed.